Effects of iodine dopant on atmospheric pressure plasma polymerized pyrrole in remote and coupling methods. (12th December 2018) - Kim, Dong Ha; Park, Choon-Sang; Jung, Eun Young; Shin, Bhum Jae; Kim, Jae Young; Bae, Gyu Tae; Jang, Hyo Jun; Cho, Byung-Gwon; Tae, Heung-Sik
Abstract: This paper investigated the chemical bonding features and conductivity characteristics of atmospheric pressure plasma (APP) conducting polymerized polypyrrole (pPPy) by iodine (I2 ) doping method in coupling and remote conditions, respectively. The I2 doped APP pPPy film surfaces were analyzed by field-emission scanning electron microscopy (FE-SEM). Fourier transform infrared spectroscopy (FT-IR), X-ray photoelectron spectroscopy (XPS), and X-ray diffraction (XRD) analyses were used to determine the crystallinity and chemical bond of I2 doped APP pPPy film for both coupling and remote conditions, respectively. In terms of crystallinity and bonding structure, I2 doped APP pPPy film, which was obtained by coupling condition, had own advantages, such as existence of abundant multiple bond (C≡C/C≡N) with π-electron, improved crystallinity, and lower initial resistance compared to that of remote condition. Whereas, the dense and thick I2 doped APP pPPy film obtained by remote condition was less hydrated and shown lower resistivity change-rate under ambient air compared to that of coupling condition. Therefore, different resistivity and humidity characteristics of I2 doped APP pPPy films depending on growth condition such as remote and coupling conditions contribute to increasing the possibility of using the I2 doped APP pPPy film as flexible electrode-materials.